AMACR and HMWCK as diagnostic tool for confirming prostate adenocarcinoma in needle prostate biopsy - Rajendragiri Goswami, Parth; P. Goswami, Alpeshpuri (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: The histopathological examination is always necessary to diagnose prostate adenocarcinoma but it would be better if the diagnosis can be supported with more accuracy by Immunohistochemistry. This study has been carried out to check usefulness of AMACR and HMCK as diagnostic tool to support diagnosis of prostate adenocarcinoma. AMACR stands for alpha-methylacyl-CoA racemase and HMWCK stand for High molecular weight cytokeratin. Material and Methods: The study was done in 50 morphological diagnosed prostate adenocarcinoma cases at tertiary care hospital. AMACR and HMWCK immunohistochemistry was done in all these cases. All the data has been plotted in tabulated form and p value calculated for both AMACR and HMWCK using Fischer’s exact and chi-square test. Results: AMACR shows strong cytoplasmic immunoreactivity in almost all prostate cancer cells while HMWCK shows strong nuclear immunoreactivity in almost all benign prostatic epithelial cells. The p value in both the cases were <0.0001 suggesting strong association of AMACR and HMWCK with prostate cancer cases. Conclusion: AMACR and HMWCK both can be used to confirm morphologically diagnosed prostate adenocarcinoma cases and it should be used in all cases of prostate carcinoma to confirm the diagnosis by immunohistochemistry.